2010
DOI: 10.1037/a0021751
|View full text |Cite
|
Sign up to set email alerts
|

Links between sisters' sexual and dating victimization: The roles of neighborhood crime and parental controls.

Abstract: This study examined the extent to which a sister’s prior sexual and dating victimization is a risk factor for young women being similarly victimized and the possible factors underlying a co-occurrence. The sample involved 122 young adult Latina or African American sister pairs (244 women; ages 16–25) who resided in low-income, urban neighborhoods. Results indicated that women whose sisters had been victimized had increased risk of victimization even after controlling for neighborhood crime, parental controls, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…To assess DV, five studies used modified versions of the Conflict Tactics Scales, 8,38,40,43,48 four used the Safe Dates Scale, 6,37,39,49 and nine used one- or two-item queries about aggressive acts. 9,3436,42,4447 The remaining two studies used the Abusive Behavior Inventory 41 and the Abuse Assessment Screening Tool. 20 Eleven studies examined demographic and structural characteristics, 8,20,37,38,4349 12 examined neighborhood disorder, 6,8,9,20,35,36,3943,49 and eight examined social disorganization.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…To assess DV, five studies used modified versions of the Conflict Tactics Scales, 8,38,40,43,48 four used the Safe Dates Scale, 6,37,39,49 and nine used one- or two-item queries about aggressive acts. 9,3436,42,4447 The remaining two studies used the Abusive Behavior Inventory 41 and the Abuse Assessment Screening Tool. 20 Eleven studies examined demographic and structural characteristics, 8,20,37,38,4349 12 examined neighborhood disorder, 6,8,9,20,35,36,3943,49 and eight examined social disorganization.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…9,3436,42,4447 The remaining two studies used the Abusive Behavior Inventory 41 and the Abuse Assessment Screening Tool. 20 Eleven studies examined demographic and structural characteristics, 8,20,37,38,4349 12 examined neighborhood disorder, 6,8,9,20,35,36,3943,49 and eight examined social disorganization. 6,8,9,34,35,43,48,49 …”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…At the family level, a lack of parental monitoring is implicated, at least in terms of dating aggression among females living in high-crime communities (East, Chien, Adams, Hokoda, & Maier, 2010), as is exposure to conflict between parents (Vagi et al, 2013; Ybarra, Mitchell, Hamburger, Diener-West, & Leaf, 2011). A poor emotional bond between caregiver and child is also associated with sexually aggressive behavior (Ybarra et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Others have suggested that parents’ attitudinal conventionality also represents a social control, wherein parents’ conservative attitudes set a standard of what constitutes allowable and tolerated behavior in their children (Jessor, 1998). Indeed, attentive parental monitoring has been linked with adolescents’ lesser likelihood of dating violence victimization (Brooks-Russell et al, 2013; Chapple, 2003; Foshee et al, 2004), and the presence of two adult parental figures in the home, presumably an index of parental monitoring and supervision, has also been associated with young adult women’s reduced likelihood of sexual (East, Chien, Adams, Hokoda, & Maier, 2010) and dating violence victimization (Gover, 2004; Halpern et al, 2009). …”
Section: Introductionmentioning
confidence: 99%